Atmospheric pollution: a case study of the Municipality of São Luís do Maranhão - Pinheiro, Juarez Mota; Bittar Venturi, Luís Antônio; Galvani, Emerson (Sociedade & Natureza, 2020)
The Brazilian capitals have been presenting environmental problems of diverse orders, reverberating negatively in the life quality of its inhabitants. São Luís, the State of Maranhão’s capital, with a population of larger than 1 million citizens consists of a good example of a Brazilian capital that can coexist with environmental atmospheric problems. The research when analyzing the atmospheric pollution in the city further sought to correlate with its geographic aspects (physical and human) by comprehending that it’s only possible to discern the complexity of the problem when it’s not limited only to the pollution sources and the emitted volumes. The collected data were obtained from seven automatic stations of air quality belonging to Company Vale S/A and oriented by an evolutive and integrated analysis. The achieved results by the study indicated that the EMAP station, localized in the county’s port zone, was the sole one that presented values that exceeded the established limits by the Law with the subsequent values in percentages for Unbreathable Particles in the following years: in 2013 (68%); 2014 (87%); 20 15 (110%) and 2016 (2%). It was also possible to distinguish between the months from July to December, in the dry season, significant rises in the atmospheric pollution indexes in the order of 24,5% for Unbreathable Particles and 35% for Total Particles in Suspension. It is concluded beyond polluting sources, that in São Luís case, the rainfall and wind are climatic atributes significant in the determination the levels of pollution in the study area.